The Influence of FOMO Marketing and eWOM on Impulsive Buying Behavior of Gen Z through Perceived Value: Insights from TikTok Users in Indonesia - Keiza Zeta Lazuardi; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In today’s digital age, consumer needs and preferences have evolved significantly due to the growing influence of social media. TikTok has become a prominent platform among Generation Z, who are known for their digital fluency and engagement with online trends. This research explores the influence of Fear of Missing Out (FOMO) marketing and Electronic Word of Mouth (eWOM) on the impulsive purchasing behavior of Generation Z on TikTok, with perceived value acting as an intervening variable. Utilizing a quantitative approach, data were collected from 110 Gen Z respondents in Jakarta. The results indicate that FOMO marketing and eWOM have a significant impact on impulsive purchasing decisions. FOMO marketing enhances perceived value by instilling urgency, while eWOM boosts trust through peer recommendations. However, perceived value does not mediate the impact of these factors on impulsive behavior, implying that emotional triggers and social influences are more direct motivators. This research underscores TikTok's role as a catalyst for impulsive buying, driven by its personalized algorithm and dynamic social interactions, offering insights for brands targeting Gen Z in the digital marketplace.